Cooperation in port wine distribution - Sequeira, L.; Crespo de Carvalho, J. (Journal of Wine Research, 2012)
The main purpose of this study is to research buyer-seller cooperation in the distribution of port wine. Eight research hypotheses were derived from data collected by a case study and incorporated into a quantitative questionnaire distributed to commercial directors of 52 producer companies and 49 distributors. A binary probit model was developed to analyse the Likert-scaled answers in valid questionnaires returned by 32 producer respondents and 29 distributor respondents. The results of the study show that (1) conflict, when permanent and intense, inhibits the development of cooperative relationships; (2) trust is likely to solve conflicts; (3) a combination of trust and adaptation increases the potential for cooperation and (4) the presence of a foreign employee at the interface between producers and distributors does not negatively affect the level of cooperation. Lastly, cooperation can be considered as an important means of developing skills and resources, which can then be applied to existing transactional relationships.